Ozidanie peremen: O situacii v sportivnoj nauke, ee prioritetach i perspektivach razvitija VNIIFKa - Aristova, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The author of the article - the director of major in the Soviet Union, and now and in the Russia, the research organization in the area of sports, analyzes the situation in the sports science. She tries not only to reveal the reasons of the occurred changes, but also shows the real ways of the solving of the problem situations. The author marks direct dependence of sports successes of the country on the degree of the development of the sports activity's scientific support. The article mentions the tendencies planned both in the sports science, and in all branches of scientific knowledge.